Angular dependence of the domain wall depinning field in sensors with segmented corners - Heinze, D.; Borie, B.; Grimm, H.; Wahrhusen, J.; Klaeui, M. (Journal of Physics: Conference Series, 2017)
Rotating domain wall based sensors that have recently been developed are based on a segmented looping geometry. To determine the crucial pinning of domain walls in this particular geometry, we investigate the depinning under different angles of an applied magnetic field and obtain the angular dependence of the depinning field of the domain walls. Due to the geometry, the depinning field not only exhibits an 180°-periodicity but a more complex dependence on the angle. The depinning field depends on two different angles associated with the initial state and the segmented geometry of the corner. We find that depending on the angle of the applied field two different switching processes occur and we can reproduce the angular dependence using a simple model calculation.
CRIS-Team Scopus Importer:2023-03-27